Penerapan Metode Bil Qolam Dalam Upaya Meningkatkan Kemampuan Membaca Al-Qur’an Di Taska Al-Fikh Orchard Ayer Tawar Perak - Putri, Mia Ananda (Al-Ulum: Jurnal Pendidikan Islam, 2023)
The objectives of this research: 1) Explain the plan for implementing the Bil Qolam method to improve the ability to read the Al-Qur'an. 2) Explain the application of the Bil Qolam method to improve the ability to read the Al-Qur'an, 3) Describe and evaluate the application of the Bil Qolam method to improve the ability to read the Al-Qur'an at Taska Al-Fikh Orchard Ayer Tawar Perak, Malaysia.This research uses descriptive qualitative research methods and types. Process analysis starting from planning, implementing and evaluating learning activities in the classroom using the Bil Qolam method, as well as data collection techniques using participatory observation, in-depth interviews and documentation. The data validation technique used in this research is the source triangulation technique.